The Test–Retest Reliability of the Peyronie's Disease Questionnaire. (17th November 2014) - Coyne, Karin S.; Currie, Brooke M.; Thompson, Christine L.; Smith, Ted M.
Abstract Introduction The Peyronie's Disease Questionnaire (PDQ) is a disease‐specific, patient‐reported outcome instrument designed to measure the psychosexual consequences and treatment outcomes of Peyronie's disease (PD). Aim The aim of this study was to evaluate the test–retest reliability of the PDQ. Methods Adult men with PD were recruited through eight clinical sites across the United States. Participants completed the PDQ during two study visits scheduled 7 (±3) days apart. At Visit 1, participants completed a sociodemographic questionnaire, the PDQ, and the International Index of Erectile Function (IIEF). At Visit 2, participants repeated the PDQ and completed an Overall Treatment Effect (OTE) scale. Test–retest reliability of the PDQ was assessed in a stable subsample (as determined by responses to the OTE). Intraclass correlation coefficients (ICCs) were calculated to evaluate the degree of association between the three PDQ subscale scores at Visits 1 and 2. Internal consistency of the subscales was also evaluated using Cronbach's alpha. Main Outcome Measure The main outcome measure was the PDQ. Results Of the 61 PD patients (mean age 59.3) who took part in the study, the majority were not receiving treatment for their PD (n = 35, 57.4%). The sample's mean score on the erectile function domain of IIEF was 19.7 (±8.2), indicating mild–moderate dysfunction. Nearly two‐thirds reported penile pain at baseline (n = 37, 63.8%). Of the participants with baseline PDQ data and who had engaged in vaginal intercourse in the past 3 months, 57 completed both study visits. The PDQ demonstrated excellent test–retest reliability in 53 stable patients. The ICC was 0.85 for the Psychological and Physical Symptom subscale, 0.89 for the Peyronie's Symptom Bother subscale, and 0.88 for the Penile Pain subscale. The Cronbach's alpha estimates for all three subscales were acceptable at the >0.70 level. Conclusions The PDQ is a highly reproducible measure of PD and can be an effective end point in clinical trials evaluating treatments for PD. Coyne KS, Currie BM, Thompson CL, and Smith TM. The test–retest reliability of the Peyronie's Disease Questionnaire. J Sex Med 2015;12:543–548.